Arthritis and antinuclear antibodies (ANA) with inherited deficiency of the sixth component of complement (C6). Issue 5 (May 1986) - Reinitz, E; Lawrence, M; Diamond, B; Keiser, H; Alper, C
Abstract : We report here the case of a woman with joint pains found to have antinuclear antibodies and undetectable serum haemolytic complement. Investigation of her and her family members showed an inherited deficiency of C6.